Advanced strength and conditioning an evidence-based approach - Turner, Anthony (Anthony N.); Comfort, Paul (Routledge, 2018)
Becoming an effective strength and conditioning practitioner requires the development of a professional skills set and a thorough understanding of the scientific basis of best practice. Aimed at advanced students and beginning practitioners, this book explores the latest scientific evidence and applies it to exercise selection and programming choices across the full range of functional areas in strength and conditioning, from strength and power to speed and agility.